IMPROVING THE LEGISLATION OF THE KYRGYZ REPUBLIC ON ORPHANS AND CHILDREN DEPRIVED OF PARENTAL CARE - Osmonalieva N. Zh.; Atabekov K.; Osmonalieva A. Zh. (Scientific Journal of Pedagogy and Economics, 2021)
Using analysis, synthesis, historical legal, law and sociological methods, unfavourable factors in Kyrgyz society are studied contribute to the appearance of orphans and children left without parental care, such as divorce of parents, growth of percentage of single-parent families, unemployment, poverty, alcohol and drug addiction, child violence in families (physical, psychological, sexual abuse), migration and others. The most significant and relevant aspects of organizing the placement of orphans and children deprived of parental care, related to adoption and foster families in Kyrgyzstan, as well as the problems of state children’s institutions of the Kyrgyz Republic are considered. The necessity of improving legislation on orphans, children deprived of parental care and the development of relatively new forms of device for orphans, children deprived of parental care (foster family) is being studied. The authors notes that in the Kyrgyz Republic insufficient attention is paid to the forms of placement of orphans in families, for example, over the eight years of the existence of foster families, their number was 57, and the number of children transferred was only 167, which is caused by insufficient material base and small wages foster parents paid by the state, which makes this institution unattractive. Transfer for adoption to a family is not always realized, since in such institutions 94% of children have parents. In this connection, it is not possible to completely eliminate or reduce the number of state-run children’s institutions for orphans and children left without parental care in the Kyrgyz Republic.